2002
DOI: 10.1577/1548-8675(2002)022<0750:poapbw>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Predation on Age-0 Paddlefish by Walleye and Sauger in a Great Plains Reservoir

Abstract: From July to October 1994 and 1995, the food habits of walleye Stizostedion vitreum, sauger S. canadense, northern pike Esox lucius, and channel catfish Ictalurus punctatus were studied in Lake Sakakawea, a Missouri River main‐stem reservoir in North Dakota. In 1994, no paddlefish Polyodon spathula were found in stomachs of these predators. In 1995, 3% of the walleyes, 12% of the saugers, and 1% of the channel catfish with identifiable prey ate wild age‐0 paddlefish. Walleyes ate paddlefish from August to Octo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…Predation may be one important reason why the age‐0 and age‐1 paddlefish in this study allocated energy to growth in length. In Lake Sakakawea, age‐0 paddlefish, and even some age‐1 fish, have been shown to be highly vulnerable to predation from walleye Sander vitreus (Mitchill, 1818) , sauger Sander canadensis (Griffith and Smith, 1834), and other species (Mero, Willis, & Power, ; Parken & Scarnecchia, ). The presence of these large predators may create a situation where overcoming predator gape limit by growing larger as rapidly as possible is beneficial within the constraints of overwinter survival their first year.…”
Section: Discussionmentioning
confidence: 99%
“…Predation may be one important reason why the age‐0 and age‐1 paddlefish in this study allocated energy to growth in length. In Lake Sakakawea, age‐0 paddlefish, and even some age‐1 fish, have been shown to be highly vulnerable to predation from walleye Sander vitreus (Mitchill, 1818) , sauger Sander canadensis (Griffith and Smith, 1834), and other species (Mero, Willis, & Power, ; Parken & Scarnecchia, ). The presence of these large predators may create a situation where overcoming predator gape limit by growing larger as rapidly as possible is beneficial within the constraints of overwinter survival their first year.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of large GFBs in both stocks is highest per unit fish weight and per gonad weight in young recruits ( Figure 9A,B), suggesting that once the fish grow large enough to escape predation (Parken and Scarnecchia, 2002), significant reviews in fisheries science vol. 19 3 2011…”
Section: Metabolic Demand Energy Allocation the Cost Of Reproductiomentioning
confidence: 99%
“…Tidwell and Mims (1990) reported that paddlefish fingerlings (9-15 cm TL) did not survive, probably owing to predation, when stocked with channel catfish Ictalurus punctatus (greater than 38 cm TL) in polyculture. Meanwhile, in Lake Sakakawea, a Missouri River reservoir, walleye Sander vitreus and sauger S. canadense consumed age-0 paddlefish up to 305 mm TL (Mero et al 1994;Parken and Scarnecchia 2002).…”
Section: Population Assessmentmentioning
confidence: 99%